2020
DOI: 10.1002/mds.28188
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Loss in Primary Tauopathies Revealed by [11C]UCB‐J Positron Emission Tomography

Abstract: A BS TRACT: Background: Synaptic loss is a prominent and early feature of many neurodegenerative diseases. Objectives: We tested the hypothesis that synaptic density is reduced in the primary tauopathies of progressive supranuclear palsy (PSP) (Richardson's syndrome) and amyloid-negative corticobasal syndrome (CBS). Methods: Forty-four participants (15 CBS, 14 PSP, and 15 age-/sex-/education-matched controls) underwent PET with the radioligand [ 11 C]UCB-J, which binds to synaptic vesicle glycoprotein 2A, a ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 72 publications
(91 citation statements)
references
References 65 publications
7
61
0
Order By: Relevance
“…Post-hoc paired T-Tests of the regional Fisher's transformed Cohen's D indicated that the regional effect sizes were significantly larger for ODI compared to grey matter atrophy ( Figure 3C). As expected, the PSP-RS group showed extensive and severe reductions of [ 11 C]UCB-J BP ND across the cortex and subcortical regions compared to controls, replicating our previous findings in a smaller sample (Holland et al, 2020). Across the whole brain, reductions in [ 11 C]UCB-J BP ND yielded the largest effect size relative to both ODI and grey matter atrophy.…”
Section: Group Comparisons Of Grey Matter Atrophy Odi and [ 11 C]ucbsupporting
confidence: 87%
See 2 more Smart Citations
“…Post-hoc paired T-Tests of the regional Fisher's transformed Cohen's D indicated that the regional effect sizes were significantly larger for ODI compared to grey matter atrophy ( Figure 3C). As expected, the PSP-RS group showed extensive and severe reductions of [ 11 C]UCB-J BP ND across the cortex and subcortical regions compared to controls, replicating our previous findings in a smaller sample (Holland et al, 2020). Across the whole brain, reductions in [ 11 C]UCB-J BP ND yielded the largest effect size relative to both ODI and grey matter atrophy.…”
Section: Group Comparisons Of Grey Matter Atrophy Odi and [ 11 C]ucbsupporting
confidence: 87%
“…Both conditions are associated with cortical and subcortical atrophy (Jabbari et al, 2019) but we have previously shown significant widespread presynaptic loss extending beyond atrophic areas (Holland et al, 2020) concordant with findings from studies utilising electromagnetoencephalography where impairment in cortical physiology is seen in both atrophic and minimally atrophic regions (Cope et al, 2018;Hughes et al, 2014;Sami et al, 2018). Having illustrated presynaptic loss as a potential explanation for impairment in cortical physiology, we aimed to investigate the synaptic bouton at large by also focusing on .…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…In-vivo estimates of regional synaptic density in the human brain were obtained from positron emission tomography (PET) with the radioligand [ 11 C]UCB-J ((R)-1-((3-(methyl-11 C)pyridin-4-yl)methyl)-4-(3,4,5-trifluorophenyl)pyr-rolidin-2-one) 49 . This ligand quantifies synaptic density 23 based on its affinity for the presynaptic vesicle glycoprotein 2A (SV2A) which is ubiquitously expressed in all brain synapses 25 .…”
Section: Synaptic Density From Positron Emission Tomographymentioning
confidence: 99%
“…The research protocol was approved by an NHS Research Ethics Committee (REC:18/EE/0059) and the Administration of Radioactive Substances Advisory Committee (ARSAC), and all participants provided written informed consent in accordance with the Declaration of Helsinki. Participant recruitment and exclusion criteria are described in detail in the original publication49 . Here, we included data from the healthy volunteers (N=15, 8 females; age: 68 ± 7 years).The radioligand [ 11 C]UCB-J was synthesised at the Radiopharmacy Unit, Wolfson BrainImaging Centre, Cambridge University, using the methodology previously described24 .…”
mentioning
confidence: 99%